2019
DOI: 10.17058/reci.v9i2.12127
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological overview of chagas disease in the state of Amazonas, from 2004 to 2014

Abstract: Justificativa e Objetivos: A doença de Chagas (DC), causada pelo Trypanosma cruzi, protozoário flagelado, descoberto a mais de 100 anos, sendo ela difundida nas américas, principalmente na américa do Sul, acometendo milhões de pessoas pelo mundo. É cada vez mais crescente o número de indivíduos acometidos com a DC na região da Amazônia Ocidental e estão relacionados a diversos fatores, porém o consumo de bebida contaminada é a principal parcela de contribuição para a elevação nos registros da doença na região.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 19 publications
2
6
1
7
Order By: Relevance
“…Another important factor reported in this study is that CD was more prevalent during December and April, and this finding is similar to that in another study conducted in the state of Amazonas in a different period 15 . Meanwhile, Oliveira et al (2018) observed greater seasonality of CD in the month of June, possibly because the outbreaks that occurred in the region during that period were due to an oral transmission.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Another important factor reported in this study is that CD was more prevalent during December and April, and this finding is similar to that in another study conducted in the state of Amazonas in a different period 15 . Meanwhile, Oliveira et al (2018) observed greater seasonality of CD in the month of June, possibly because the outbreaks that occurred in the region during that period were due to an oral transmission.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, CD was predominant in men, and this may be related to the participant's work activities, such as extraction of açaí and piassava; these activities increases the men's exposure to the vector and consequently to CD. In similar surveys conducted in the states of Pará 13 and Acre 14 , the highest frequency was also reported in men; this finding is not consistent with the results of another survey conducted in Amazonas, which reported that women had higher exposure to CD 15 . This higher occurrence in men may be related to their work activities, such as extraction of natural products, which increases the possibility of contact with the disease vector.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…The oral infection route has configured the main form of transmission and a serious public health problem (Menezes, et al 2019), due to the increase in the rates of the disease from 129 cases (2012) to 298 cases (2016) (Brasil, 2019). Among the foods, the contamination of the pulp or juice of açai (Euterpe oleracea) stands out, which during the period from 2007 to 2016 had an increase of 99.57%.…”
Section: Introductionmentioning
confidence: 99%